How Digital Engagement Shapes Loyalty: The Combined Influence of Live Streaming and Influencer Marketing on Repurchase Behavior in TikTok Shop - Okta Mahardika Firmanda; Nuri Purwanto (Proceeding International Conference on Digital Education and Social Science, 2025)
This study aims to analyse the effect of live streaming and influencer marketing on repeat purchase interest in Skintific products on TikTok Shop among Generation Z in Jombang. The scope of the study focuses on Gen Z consumers who have purchased Skintific products through the TikTok Shop platform. The research method used was explanatory quantitative with primary data collection through an online questionnaire of 100 respondents selected purposively. The data were analysed using multiple linear regression analysis with the help of SPSS. The results showed that both live streaming and influencer marketing had a positive and significant effect on repurchase intention, with a coefficient of determination (R²) of 0.520. Simultaneously, both variables were able to explain 52% of the variation in repurchase intention. The research conclusion confirms that digital marketing strategies through live streaming and influencer collaborations are effective in increasing loyalty and repurchase intention for Skintific products among Gen Z. The implications of this research can be used as a reference for companies in developing more interactive and trustworthy promotional strategies on social media platforms.